The impact of green supply chain management practices on performance: moderating role of institutional pressure with mediating effect of green innovation - Shafique, Muhammad; Asghar, Muhammad; Rahman, Haji (Business, Management and Economics Engineering, 2017)
Green supply chain management (GSCM), a cross-disciplinary field has grown during recent years with increasing interest from both academia and industry. GSCM considers emphasizing environmental issues in Traditional Supply Chain Management (TSCM). Due to the new trends in global warming, environmental sustainability has become a greater concern among the organizations and enterprises globally. This study will focus on green supply chain management practices in the presence of green innovation. Green innovation will improve organizational processes as well as products, which lead to economic and environmental performance. Different institutional actors are putting pressures to implement Green supply chain management practices. Population of this study is electronics industry in Pakistan. Sample size is 500 with cluster sampling technique. Data has been collected through a survey method based on the adopted questionnaire. The collected data will be tested through Cronbach Alpha, Descriptive Statistics, Pearson Correlation, Linear Regression, Moderated Regression, Multiple Logistic Regression and Hayes’s statistical tests to analyse the suggested research model. This study will enable organizations to implement green supply chain management practices to bear institutional pressure and move towards green innovation to enhance their economic and environmental performance that were never possible before this study.